Reinsurance in Managing Catastrophe and Financial Risk in the Polish Market During the Years 2010-2014 - Grzebieniak, Andrzej (Olsztyn Economic Journal, 2015)
Reinsurance plays an important role in managing the risk in an insurance company. Its crucial importance is especially visible in the situation when there is a growth of catastrophic and financial risks on the market. Such a situation has occurred in the Polish market since 2010. In order to achieve financial stabilisation, insurance companies apply reinsurance more frequently so they cede the risk on the reinsurer together with an appropriate part of the premium for the given risk. Catastrophic risk includes, among others, the following groups of insurance: class II- 5, 8, 9, 11 and financial risk in groups 14 and 15. In those insurance groups, the range of reinsurance applied (measured with a percentage of premium given to reinsurers by insurance companies and the percentage of damages received from them in relation to total paid out compensations) was the highest in the analyzed period of time. Research confirmed the hypothesis that together with the growth of catastrophic and financial threats in the Polish economy the range of reinsurance applied in insuring those risks also increases.